2012
DOI: 10.1371/journal.pone.0048406
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Triploidy in Western North American Aspen (Populus tremuloides)

Abstract: We document high rates of triploidy in aspen (Populus tremuloides) across the western USA (up to 69% of genets), and ask whether the incidence of triploidy across the species range corresponds with latitude, glacial history (as has been documented in other species), climate, or regional variance in clone size. Using a combination of microsatellite genotyping, flow cytometry, and cytology, we demonstrate that triploidy is highest in unglaciated, drought-prone regions of North America, where the largest clone si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 69 publications
8
100
2
Order By: Relevance
“…They occur in mixed forests as well as monospecific stands that can extend continuously over broad areas; the largest individual organism known to science, the Pando genet, covers 44.3 ha in southern Utah, USA [42]. Western US aspen are often triploid and form expansive genets of genetically identical ramets [43][44][45]. Conversely, aspen in the Great Lakes region of the USA are rarely triploid [44], and form small genets that are often interspersed with mixed northern hardwood species.…”
Section: (C) Above-and Below-ground Linkages In Aspen Forestsmentioning
confidence: 99%
See 2 more Smart Citations
“…They occur in mixed forests as well as monospecific stands that can extend continuously over broad areas; the largest individual organism known to science, the Pando genet, covers 44.3 ha in southern Utah, USA [42]. Western US aspen are often triploid and form expansive genets of genetically identical ramets [43][44][45]. Conversely, aspen in the Great Lakes region of the USA are rarely triploid [44], and form small genets that are often interspersed with mixed northern hardwood species.…”
Section: (C) Above-and Below-ground Linkages In Aspen Forestsmentioning
confidence: 99%
“…During a 1 year period from 2005 to 2006, the San Juan National Forest in Colorado experienced a 58% increase in area of recent aspen mortality [50]. That aspen decline and triploidy co-occur is not inconsequential; physiological traits associated with polyploidy may influence drought susceptibility, making regional declines in aspen a potential threat to genetic variation and persistence in aspen [44].…”
Section: (C) Above-and Below-ground Linkages In Aspen Forestsmentioning
confidence: 99%
See 1 more Smart Citation
“…We restricted the sample area for three reasons: (1) in the western United States, most of the aspen populations are found in these eight states; (2) these populations appear to be genetically distinct from populations in Canada and the northeastern United States (Mock et al 2012);and (3) all FIA plots in this region were sampled by the Rocky Mountain Research Station, minimizing differences in sampling protocols. To maximize the opportunity of observing climatic impacts on mortality indices, we examined FIA plots measured after 2002, when regional declines were observed to increase (Hogg et al 2008, Worrall et al 2008).…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
“…The first North American triploid quaking aspen (P. tremuloides) were found in northeastern Minnesota ( VAN BUIJTENEN et al, 1957;EINSPAHR et al, 1963) and later in Utah (EVERY and WIENS, 1971). In recent studies, high rates of triploidy (up to 69 % of genets) were demonstrated in P. tremuloides across the western USA (MOCK et al, 2012). Natural well-growing triploids of Populus tomentosa were first discovered in China (ZHU et al, 1998;YAO and PU, 1998).…”
Section: Introductionmentioning
confidence: 99%